Catalysing the development and introduction of paediatric drug formulations for children living with HIV: a new global collaborative framework for action. Issue 5 (May 2018) - Penazzato, Martina; Watkins, Melynda; Morin, Sébastien; Lewis, Linda; Pascual, Fernando; Vicari, Marissa; Lee, Janice; Hargreaves, Sally; Doherty, Meg; Siberry, George K
Summary: Progress in the development and introduction of paediatric formulations for key infectious diseases is poor in low-income and middle-income countries (LMICs). Although major steps have been made in the scale-up of antiretroviral medicines in LMICs, the development and deployment of formulations for infants and children is suboptimal. Of the children living with HIV globally (most in Africa), only 43% are receiving antiretroviral therapy (ART), many with suboptimal formulations. These shortfalls pose a series of challenges to meeting global treatment targets of 1·6 million children (aged 0–14 years) on ART by the end of 2018 (95% coverage) and to ensuring that 95% of those on ART are virologically suppressed. The Global Accelerator for Paediatric Formulations (GAP-f) has been developed to accelerate research, development, regulatory filing, introduction, and uptake of prioritised paediatric antiretrovirals in age-appropriate formulations by 2020, with innovative, strategic, and sustainable financing. The GAP-f will build on existing efforts to maximise coordination and alignment of policy makers, research networks, regulatory agencies, funding organisations, and manufacturers in paediatric HIV and other paediatric diseases, including tuberculosis, viral hepatitis, and other infectious diseases. Paediatric drug development and scale-up will require special efforts to bring greater visibility and new solutions to ensure that children in LMICs have access to effective and appropriate treatment options.